2015
DOI: 10.1080/03602559.2014.986802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Fillers on Crystallization Properties and Thermal Conductivity of Poly(phenylene sulfide)

Abstract: Differential scanning calorimetry and polarized optical microscopy methods were used to investigate the crystallization behavior and isothermal crystallization kinetics of poly (phenylene sulfide) (PPS)/carbon nanotube (CNT) and PPS/CNT/carbon fiber (CF) composites. In this article, the influences of CNT and CF on PPS crystallization behavior are explained. The thermal conductivity properties of composites were studied using the laser flash method. The results show that CNT increased crystallization temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The heat of fusion of crystalline PPS is 76.5 J/g [28]. Since the MWCNTs act as nucleation agents, many studies have reported that MWCNTs can promote the crystallization via the nucleation effect [29,30,31]. The experimental data were consistent with the reports on the nucleation effect of the MWCNTs.…”
Section: Resultssupporting
confidence: 77%
“…The heat of fusion of crystalline PPS is 76.5 J/g [28]. Since the MWCNTs act as nucleation agents, many studies have reported that MWCNTs can promote the crystallization via the nucleation effect [29,30,31]. The experimental data were consistent with the reports on the nucleation effect of the MWCNTs.…”
Section: Resultssupporting
confidence: 77%
“…With the continuous increase of GQDs content, the dispersion of GQDs in PPS/GQDs nanocomposites decreases and agglomeration occurs, which is not conducive to stress transfer, resulting in poor stress concentration points and the reduction of tensile strength and impact strength. [ 53 ]…”
Section: Resultsmentioning
confidence: 99%
“… where , , and represent the weight percentage of the PPS, the heat of fusion at the melting point of the PPS/MWCNTs/AlN composites, and the heat of fusion of the crystalline PPS, which was known as 76.5 J/g [ 38 ], respectively. Many studies have reported that the MWCNTs, which is a nucleation agent, can facilitate the crystallization by the nucleation effect [ 11 , 34 , 39 , 40 ]. The experimental data were consistent with the literatures on the nucleation effect of the MWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Kostagiannakopoulou et al and Ciecierska et al conducted a study to improve the thermal conductivity from 0.29 W/mK for neat epoxy to 0.36 W/mK for 3 wt % MWCNTs loaded epoxy composites and 0.13 W/mK for neat epoxy to 0.24 for 5 wt % MWCNTs loaded epoxy composites [ 9 , 10 ]. Deng et al conducted the study to improve thermal conductivity and crystallization properties by introducing carbon based filler such as MWCNTs, and carbon fiber on the PPS matrix [ 11 ]. However, the covalent functionalization was widely used for modifying the surface of the MWCNTs because the MWCNTs can be easily aggregated with themselves, which adversely affected the thermal properties of the polymer nanocomposites, due to strong van der Waal’s interactions between individual tubes [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%